The impact of myenglishstep.com and Yenni's English content to students’ descriptive writing skills of HOTS - Amin Wibowo; Senowarsito Senowarsito; Suwandi Suwandi (Universitas Islam Sultan Agung, 2023)
This study aimed to determine the effectiveness of myenglishstep.com and Yenni's English content towards students’ descriptive writing skills of Higher Order Thinking Skills (HOTS) at SMPN 42 Semarang. In this research, a quasi-experimental study design was used. This was a quantitative study that compares Experimental Group 1 and Experimental Group 2, constructed using myenglishstep.com model treatment and Yenni Dwi Maria's English Content at sumber.belajar.kemdikbud.go.id model therapy, respectively. The sample was taken through a purposive sampling technique. The test was done for both experimental classes. The pre-test was carried out before the treatment in data collection. The present researchers used a t-test of SPSS to test the hypothesis in data analysis. Based on the results of the t-test, it was found sig. (2-tailed) = 0.001 < sig. 0.05. It means there is a significant difference between the pre-test and post-test data (H0 rejected, Ha accepted). It can be concluded that myenglishstep model and Yenni’s content for the seventh-grade students effectively improved students’ descriptive writing skills of HOTS.